2022
DOI: 10.1038/s41415-022-3993-4
|View full text |Cite|
|
Sign up to set email alerts
|

Through the looking glass: a review of the literature surrounding reflective practice in dentistry

Abstract: Reflection is an essential component of the learning process that helps to elicit deeper learning. In healthcare, this uses experiential activities to produce knowledge that compels the clinician to change their practice. Deep reflection allows one to explore emotions associated with challenging learning experiences, empowering reinterpretation of these experiences and removing barriers to further learning. Reflection is a key requirement of dental education at all stages. This paper aims to explore the existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A recent literature review highlighted the need for a systematic overhaul of current methods of facilitating reflective practice in dentistry [10]. Furthermore, qualitative research by this team has demonstrated that the use of a written clinical logbook (Figure 1) to engage undergraduate dental students in deep reflection is unhelpful [11].…”
Section: Background and Need For Innovationmentioning
confidence: 99%
“…A recent literature review highlighted the need for a systematic overhaul of current methods of facilitating reflective practice in dentistry [10]. Furthermore, qualitative research by this team has demonstrated that the use of a written clinical logbook (Figure 1) to engage undergraduate dental students in deep reflection is unhelpful [11].…”
Section: Background and Need For Innovationmentioning
confidence: 99%
“…This could be used to develop their own practice as well as to identify evidence‐based care improvements to inform care planning and practice for individual residents. Reflection is an established approach to learning (Campbell & Rogers, 2022; Moon, 2004; Schon, 1991) and the development of individual practice across a range of sectors (Kraft et al, 2021). Reflection with a mentor or supervisor is a well‐established mechanism for personal development and support within health and care services but is relatively unexplored in the context of delivery and embedding of person‐centred dementia care (Edgar et al2023).…”
Section: Discussionmentioning
confidence: 99%
“…A key aspect of transitional stress at this stage has been related to unfamiliarity with clinical settings and lack of knowledge reported by students 14 . Deep reflection could play an important role in helping dental students to navigate this transition 15 . There are however suggestions that deep reflection is not well supported in current dental curricula 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Deep reflection could play an important role in helping dental students to navigate this transition 15 . There are however suggestions that deep reflection is not well supported in current dental curricula 15,16 . Much of what dental students learn may relate to their observations of the clinical culture, including interactions of staff and other students with their patients and clinical tasks 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation